Self-Attitude as Imperative Modus of Professional Identifica-tion of a Personality - Virna, J. P. (Psychological Prospects Journal, 2011)
The content of self-attitude as imperative modus of pro-fessional identification is disclosed in the article. Self-attitude is proved to be deter-minant motivational factor of professional identification integrally characterizing complex of psychological communicative qualities of a pedagogue personality.
Keywords: self-attitude professional identification pedagogue